2019
DOI: 10.1088/1755-1315/374/1/012054
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of biomass and carbon potential on eucalyptus stand in industrial plantation forest, North Sumatra, Indonesia

Abstract: Forests degradation causes forestry businesses to be economically less profitable than other agribusiness commodities, thus triggering the policies of governments that plan to convert natural forests to other uses, such as industrial forest plantations. The purpose of this study was to determine the potential of biomass and carbon stores in eucalyptus stands in industrial plantation forests, North Sumatra, Indonesia. This research was carried out in Industrial Plantation Forest of Toba Pulp Lestari Areas, Toba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…affect the aboveground biomass carbon. Some researchers indicated that differences of carbon stocks in plant stands depend on part of plant (Muhdi et al 2019) and improved forest management can diminish CO2 emissions Putz et al (2008) and stand damages (Purwoko et al 2018).…”
Section: Understorey Plant Carbonmentioning
confidence: 99%
“…affect the aboveground biomass carbon. Some researchers indicated that differences of carbon stocks in plant stands depend on part of plant (Muhdi et al 2019) and improved forest management can diminish CO2 emissions Putz et al (2008) and stand damages (Purwoko et al 2018).…”
Section: Understorey Plant Carbonmentioning
confidence: 99%
“…In addition, the harvesting waste can also occur due to the determination of the wrong felling direction, thus causing the wood to break during logging. In addition, in forest harvesting activities, problems often occur because the equipment used stop working due to lack of maintenance of the forest harvesting tools [6]. According to the research by [7] and [8] resulted that the occurrence of a large amount of logging waste and residual stand damage caused by technique of felling and determining the direction of felling.…”
Section: Volume and Percentage Of Wood Wastementioning
confidence: 99%
“…Logging activities are mostly done using mechanical cutting tools, ranging from chainsaws to harvester [3]. Several studies have shown that timber harvesting causes environmental damage including to residual stands and forest biomass [4,5,6].…”
Section: Introductionmentioning
confidence: 99%